The social value of zoos - Fraser, John 1960-; Switzer, Tawnya 1977- (Cambridge University Press, 2021)
Combining anecdotes with scientific data, this book is a journalistic inquiry into what is currently known about zoos and aquariums as sociocultural intersections of mission, public perception, and on-site meaning making. The authors draw on conservation psychology and other social science research to explore how zoos might develop and deliver more effective learning experiences to promote and nurture conservation values and collective action. While people use zoos with specific priorities and motivations in mind, these are social settings. Indeed, it is because they represent an important, vast, and trusted social enterprise that zoos have such powerful opportunities to change how diverse public audiences view, value, identify, and engage with animals and the broader biophysical environment
Title from publisher's bibliographic system (viewed on 26 Mar 2021)
Keywords: Zoos / Social aspects